Knobloch syndrome associated with Polymicrogyria and early onset of retinal detachment: two case reports. Issue 1 (December 2017) - White, Robert; Wang, Yao; Tang, Peter; Montezuma, Sandra
Abstract Background Knobloch Syndrome (KS) is a rare congenital syndrome characterized by occipital skull defects and vitreoretinal degeneration. Retinal detachment (RD) often occurs at the end of the first decade of life or later. Aside from occipital skull defects, central nervous system abnormalities are uncommon. Case presentations We report on two siblings with KS. The first, a seven month old male, presented with nystagmus and was found to have a serous RD and a tessellated retinal appearance. His sister had a history of multiple visual abnormalities and had a similar retinal appearance although no signs of RD, but retina staphylomas. Genetic testing performed on both siblings showed a mutation inCOL18A1, diagnostic of KS. MRI of both siblings demonstrated polymicrogyria but did not show occipital defects. Conclusions Although several families with KS have been described previously, our case is noteworthy for several reasons. The RD observed in our first patient occurred at an early age, and we find evidence of only one patient with KS who had an RD identified at an earlier age. The findings of polymicrogyria are not characteristic of KS, and we found only a few previous reports of this association. Additionally, we review potential treatment options for this condition.